Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.2337/diabetes.48.4.685
|View full text |Cite
|
Sign up to set email alerts
|

DNA demethylation during the differentiation of 3T3-L1 cells affects the expression of the mouse GLUT4 gene.

Abstract: GLUT4 is the major glucose transporter in adipose tissue and skeletal and cardiac muscles. We examined the mechanisms underlying GLUT4 gene expression in 3T3-L1 cells, which express the gene during their differentiation from preadipocytes to adipocytes. In transient transfections, the activity of a mouse GLUT4 promoter extending to -100 bp in the 5'-flanking region did not differ significantly between 3T3-L1 preadipocytes and adipocytes. Promoter activity up to -590 bp in preadipocytes and adipocytes showed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
1
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 34 publications
2
66
1
4
Order By: Relevance
“…We have also shown that GLUT4 gene transcription during adipocyte differentiation is regulated by the 96 kM r repressor protein [24]. When we examined the mechanism underlying GLUT4 gene induction during the differentiation of 3T3-L1 cells, we also found that the methylation of specific CpG sites and the methylationsensitive transcription factor contribute to GLUT4 gene regulation [5]. In this study, we found that methylation of specific CpG sites also modulated the leptin promoter activity during adipocyte differentiation.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…We have also shown that GLUT4 gene transcription during adipocyte differentiation is regulated by the 96 kM r repressor protein [24]. When we examined the mechanism underlying GLUT4 gene induction during the differentiation of 3T3-L1 cells, we also found that the methylation of specific CpG sites and the methylationsensitive transcription factor contribute to GLUT4 gene regulation [5]. In this study, we found that methylation of specific CpG sites also modulated the leptin promoter activity during adipocyte differentiation.…”
Section: Discussionsupporting
confidence: 54%
“…The molecular weight of this protein differs from those of previously reported methyl-CpG-binding proteins, including MeCP2 [28±33] but is close to that of the 55 kM r methyl-CpG-binding protein that binds to the GLUT4 gene promoter [5]. The 55 kM r protein was observed to recognize the demethylation of the GLUT4 gene during the differentiation of 3T3-L1 preadipocytes to adipocytes.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…Additionally, differential DNA methylation was observed in promoters of genes involved in glucose metabolism. These include the facilitative glucose transporter 4 [54] and the uncoupling protein 2 [55]. Both are major targets involved in the development of type 2 diabetes.…”
Section: 12mentioning
confidence: 99%